Food microbiology and food safety - Bueno, David C. (Mandaluyong City, Philippines : Books Atbp. Publishing Corp, 2014)
This textbook is a comprehensive source of insight into Microbiology that focuses on food preparation. This is instrumental in providing an overview of food safety and sanitation for HRM students.
Unit 1 Food microbiology and food safety -- Unit 2 Food safety and sanitation.
Includes bibliographical references.
Keywords: MICROBIOLOGY -- FOOD SAFETY